Biodiversity of birds of 13 de julho avenue mangrove in Aracaju, Sergipe: DOI: 10.15343/0104-7809.200832.3.7 - Melo Almeida, Bruno Jackson (2008)
One agreed to use the denomination 13 de Julho-Atalaia mangrove the mangrove extension of 13 de Julho up to the Districtof Atalaia, Aracaju (SE). In this study area, 6 fixed points were established, of which we did the identification and the counting of thenumber of individuals of each species and the characterization of the type of activity they engage in. From July 2003 to July 2004 atotal of 44 observation journeys were carried out with a minimum duration of 1 hour and a maximal of 4 hours and 20 minutes (meanduration ±2 2 h 36 m). We identified 19 families and 46 birds species, being that 17 of these were migrant coming from the Northhemisphere. Among the observed migrant species four belonged to the Charadriidae family: Charadrius semipalmatus, Charadriuswilsonia, Pluvialis squatarola, Pluvialis dominica; eleven to Scolopacidae: Calidris alba, Calidris pusilla, Calidris fuscicollis, Calidriscanutus, Arenaria interpres Numenius phaeopus, Tringa flavipes, Tringa melanoleuca, Actitis macularia, Catoptrophorus semipalmatus,Limnodromus griseus. Ardeidaes observed in mangroves can be considered residents, in spite of the variations presented by some speciessuch as Egretta thula, Florida caerulea, Casmerodius albus, Butorides striatus, Nyctanassa violaceus and Bubucus ibis.